Responsive oligochitosan nano-vesicles with ursodeoxycholic acid and exenatide for NAFLD synergistic therapy via SIRT1. (15th July 2022) - Xie, Pengchao; Peng, Yan; Qiu, Liyan
Abstract: To explore effective therapeutic strategy on nonalcoholic fatty liver disease (NAFLD), the amphiphilic oligochitosan derivative containing ursodeoxycholic acid (UDCA) was synthesized and named as UBC, which could self-assemble and encapsulate exenatide (Exe) to obtain Exe-UBC nano-vesicle. Exe-UBC could be uptaken by fatty-acid cultured cells and release UDCA and Exe responsive to the high esterase concentration. In vitro experiments demonstrated that Exe-UBC activated the expression level of SIRT1 with inhibited expression of PGC-1β and PPAR-γ and consequently exerted synergistic bioaction immediately on reducing lipidosis. After a month of Exe-UBC treated through intravenous injection, the body weight of high-fat diet feeding C57BL/6 mice recovered to ordinary level, and their lipid contents in the liver declined significantly. The recovery in hepatic function indexes like TG, AST, and ALT further revealed the superiority of Exe-UBC vesicles. These results suggested that the co-delivery of UDCA and Exe via Exe-UBC could be a potent platform for NAFLD treatment. Graphical abstract: Unlabelled Image